Pharmacological Thromboprophylaxis Effectiveness in Low-Risk Patients Underwent Arthroscopic Anterior Cruciate Ligament Reconstruction: A Randomized Clinical Trial - Mohammadreza Minator Sajjadi; Mohammad Nazarinasab; Amirali Behroozi; Amin Karimi; Amir Mehrvar; Seyed Amir Ahmad Safavi Naini (Journal of Orthopedic and Spine Trauma)
Purpose: This study aims to evaluate the effectiveness and safety of Aspirin and LMWH in an arthroscopic anterior cruciate ligament (ACL) reconstruction of low-risk patients.